2015
DOI: 10.1590/s0034-8910.2015049005172
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of surgical treatment of hip fracture in older adults

Abstract: OBJECTIVE To analyze the incremental cost-utility ratio for the surgical treatment of hip fracture in older patients.METHODS This was a retrospective cohort study of a systematic sample of patients who underwent surgery for hip fracture at a central hospital of a macro-region in the state of Minas Gerais, Southeastern Brazil between January 1, 2009 and December 31, 2011. A decision tree creation was analyzed considering the direct medical costs. The study followed the healthcare provider’s perspective and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…However, bone mass alone is not a determining factor. 3 , 4 A study by Cummengs et al 22 found that Japanese women had lower BMD than their Caucasian peers; however, the former suffered fewer fractures. Likewise, age and BMI may not be directly related to loss in bone mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bone mass alone is not a determining factor. 3 , 4 A study by Cummengs et al 22 found that Japanese women had lower BMD than their Caucasian peers; however, the former suffered fewer fractures. Likewise, age and BMI may not be directly related to loss in bone mass.…”
Section: Discussionmentioning
confidence: 99%
“… 3 This issue is relevant due to the high morbidity and mortality, high postoperative disability index, and increasing costs to society with less beneficial results related to treatment. 4 These fractures are considered one of the largest public health problems in the world. 4 According to American statistics, over 250,000 hip fractures occur each year; it is expected that over the next 30 years, there will be an increase of 100% in the number of cases/year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo conduzido nos países da União Europeia mostrou que em 2010 ocorreram 610 mil fraturas de quadril/fêmur em idosos com mais de 70 anos 14 e, no Brasil, entre 2008 e 2012, foram 38.755 fraturas de fêmur, de modo que essa ocorrência vem aumentando nas últimas décadas 2 . As fraturas são resultantes de quedas e fragilidades ósseas e têm como consequência a perda da independência e os altos índices de morbidade e mortalidade, elevando os custos para o sistema de saúde 15 . Diante dessa realidade, ressaltamos a importância da implementação das medidas preventivas recomendadas pela OMS 16 .…”
Section: Resultsunclassified
“…Considering that generic questionnaires may be applied in several situations, the EQ-5D instrument was used to evaluate QoL in older adults submitted to hip reconstruction surgeries (25) . This instrument was validated into Portuguese, showing good acceptability and validity in the health status measurement of individuals with different pathologies such as cataract, asthma, chronic obstructive pulmonary disease, and rheumatoid arthritis (26) .…”
Section: Discussionmentioning
confidence: 99%